The Home Numeracy Environment and Measurement of Numeracy Performance in English and Spanish in Dual Language Learners. (February 2021) - Kung, Melody; Stolz, Kelsey; Lin, Joyce; Foster, Matthew E.; Schmitt, Sara A.; Purpura, David J.
Some evidence suggests that the home numeracy environment (HNE) is related to children's numeracy. Socioeconomic status (SES) and language minority status can also influence children's HNE and numeracy. Limited HNE research focuses on dual language learners (DLLs). Using a sample of preschool-aged children ( n = 98) from low socioeconomic status (SES) backgrounds, we examined differences between Spanish-speaking DLLs' ( n = 37) and monolingual English speakers' ( n = 61) numeracy, differences in HNEs, and predictive role of HNE on numeracy. Using frequentist and Bayesian t tests, we found that numeracy was not significantly different between DLLs and monolingual English speakers when DLLs' numeracy was measured in English or in both English and Spanish. However, DLLs' Spanish numeracy was lower than monolingual English speakers' English numeracy, t (96) = 2.10, p = .038, Bayes factors (BF10 ) = 1.51. HNE did not significantly predict either group's numeracy regardless of assessment language. This study is an important step toward understanding DLLs' HNE and numeracy.